Penerapan Konseling Individu dengan Teknik Congnitive Restructuring untuk Mereduksi Pola Pikir Negatif Narapidana Pembunuhan - Aghniya Ahsana; Abdur Razzaq; Zhila Jannati (Scidacplus, 2023)
Negative thought patterns can result in individuals feeling like they have failed, lacking self-confidence, remembering a dark past, considering this as bad luck, giving up hope and having difficulty solving problems on their own. Researchers are trying to provide individual counseling guidance to reshape positive thinking patterns in client